STRATEGI OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI SULAWESI SELATAN DALAM MENDORONG KUALITAS PELAYANAN PUBLIK MELALUI LAPORAN MASYARAKAT - Chandra Febrianto, Muhammad (Politeknik STIA LAN Makassar, 2023)
The Ombudsman is an external government agency established to oversee the running of public services in Indonesia. In carrying out its duties, namely receiving community reports and preventing maladministration, there is a phenomenon of distribution of community reports dominated by urban communities and the results of compliance assessments which are a form of maladministration prevention are dominated by yellow predicates, especially in the South Sulawesi Representative Ombudsman. This study aims to formulate a policy strategy that must be carried out by the Ombudsman of the Republic of Indonesia Representative of South Sulawesi Province in encouraging the quality of public services through community reports. The approach in this research is qualitative with data collection techniques, namely interviews, observations and literature studies which will later be able to draw conclusions on existing problems. The results of the study show that the strategy carried out by the South Sulawesi Representative Ombudsman seen from the policy implementation model by Edward III is constrained by lack of communication, limited human resources and budget as well as several mechanisms that make it difficult to make decisions that affect the distribution of community reports in South Sulawesi.